Level of living of Polish citizens in the interwar period, and its diversification - Leszczyńska, Cecylia (Roczniki Dziejów Społecznych i Gospodarczych, 2016)
The paper focuses on the analysis of the variety of standards of living within the society of interwar Poland. These were determined primarily by individual streams of income and the scope and availability of public services. The standard of living is represented through the analysis of the range of income and remuneration within basic social and professional groups, housing conditions, and the level of schooling. It needs to be added that the image of the standard of living of various social groups is incomplete, with biggest gaps appearing in the study of small trade (merchant activity, craft, cottage industry) and some groups within the peasant population.